Circular manufacturing ecosystems: Automotive printed circuit boards recycling as an enabler of the economic development. Issue 1 (31st December 2023) - Cozza, Giorgio; D'Adamo, Idiano; Rosa, Paolo
ABSTRACT: The management of waste from electrical and electronic equipments (WEEEs) is a well-established topic in the extant literature. However, also the automotive sector is becoming a relevant source of WEEE, given the even more relevant presence of electronic components in cars. Due to new European environmental policies, end-of-life vehicles (ELVs) volumes are expected to grow in the next future, together with obsolete car electronics components. Hence, this work wants to assess the potential economic impact derived from car electronics recycling processes adopting the Net Present Value (NPV) as reference indicator. Through a detailed sensitivity and break-even point (BEP) analysis and a comparison of different cases, this work identifies a set of scenarios useful for industrial actors willing to enter the market of car electronics recycling. Results show an NPV varying from 136, 570 to 607, 621 €/t with a decisive role played by gold recovery.